Humidity sensing using plastic optical fibers - Tay, Chia Meng (2011)
The use of plastic optical fibers (POFs), curved at the sensing point and coated with cobalt chloride (CoCl2) and gelatin as the overlay material, for relative humidity sensing is demonstrated in this paper. The fiber-core diameter and bending radius of the sensing point affects the sensitivity of the sensor to a great extent.